Air pollution and low birth weight in an industrialized city in Southeastern Brazil, 2003-2006 - Marcelo Moreno dos Reis; Mariana Tavares Guimarães; Alfésio Luís Ferreira Braga; Lourdes Conceição Martins; Luiz Alberto Amador Pereira
ABSTRACT: Introduction: Birth weight is an important indicator of several conditions that manifest earlier (as fetal and neonatal mortality and morbidity, inhibited growth and cognitive development) and later in life such as chronic diseases. Air pollution has been associated with adverse pregnancy outcomes. Objective: Retrospective cohort study investigated the association between low birth weight (LBW) and maternal exposure to air pollutants in Volta Redonda city, Rio de Janeiro, Brazil, from 2003 to 2006. Methods: Birth data was obtained from Brazilian Information System. Exposure information (O3, PM10, temperature and humidity) was provided by Governmental Air Quality Monitoring System. Linear and Logistic models, adjusted for sex, type of pregnancy, prenatal care, place of birth, maternal age, parity, education, congenital anomalies and weather variables were employed. Results: Low birth weight (LBW) represented 9.1% of all newborns (13,660). For an interquartile range increase in PM10 it was found OR2 ndTrimester = 1.06 (95%CI 1.02 - 1.10), OR3 rdTrimester = 1.06 (95%CI 1.02 - 1.10) and, in O3 it was found OR2 ndTrimester = 1.03 (95%CI 1.01 - 1.04), OR3 rdTrimester = 1.03 (95%CI 1.02 - 1.04). The dose-response relationship and a reduction in birth weight of 31.11 g (95%CI -56.64 - -5.58) was observed in the third trimester of pregnancy due to an interquartile increase of O3. Conclusion: This study suggests that exposures to PM10 and O3, even being below the Brazilian air quality standards, contribute to risks of low birth weight.